The regulation of air transport - Humphreys, Barry, author.
1 online resource.
Keywords: The regulation of modern civil aviation can be traced back to the later years of the Second World War. An intense debate about the future regulatory regime resulted in a compromise which to this day essentially dictates the structure of the global airline industry. Further progress towards normalising' the industry appears to be slowing down, and perhaps even going into reverse. Without an understanding of the development of regulation, it is not possible to understand fully the industry's current problems and how they might be resolved. Many books have been written about the development of international air transport, covering deregulation, privatisation, the emergence of new business models among other things, but few if any have taken a broad view of the trends which have determined the industry's current structure. The Regulation of Air Transport charts the development of aviation from the end of the Second World War to the present day, following the key trends and disruptive forces. It provides an overview of what has determined the industry's current structure, the problems still facing the industry and the ways in which it could develop in the future. This wide-ranging study is important reading for both professionals and academics within the aviation field, as well as anyone interested in the broader development of economic regulation.